2009
DOI: 10.1111/j.1741-3729.2008.00548.x
|View full text |Cite
|
Sign up to set email alerts
|

Shadowed by War: Building Community Capacity to Support Military Families

Abstract: The context of military service has changed greatly since the events of 9/11. The forward deployment of service members to active war zones, which involves the issues of separation, time away from home, and eventual reunion, increases the vulnerability of their families to multiple, negative short‐term and long‐term effects. This article explores these issues and suggests a new approach to building support systems to support these military families. To this end, a capacity‐building framework is introduced, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
94
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 116 publications
(98 citation statements)
references
References 17 publications
1
94
0
3
Order By: Relevance
“…In its early years of development, the inventory was known as the Unit Assets Inventory, with parallel versions for AF members and the civilian spouses of these members (Personal Assets Inventory) (Huebner, Mancini, Bowen, & Orthner, 2009). The SRI received AF-wide sponsorship in 2008, which continued until 2013, from the Airman and Family Services Division (HQ AF/A1SA) as part of its Community Readiness Consultant Practice Strategy (Bowen, Martin, Liston, & Nelson, 2009).…”
Section: The Support and Resiliency Inventorymentioning
confidence: 99%
“…In its early years of development, the inventory was known as the Unit Assets Inventory, with parallel versions for AF members and the civilian spouses of these members (Personal Assets Inventory) (Huebner, Mancini, Bowen, & Orthner, 2009). The SRI received AF-wide sponsorship in 2008, which continued until 2013, from the Airman and Family Services Division (HQ AF/A1SA) as part of its Community Readiness Consultant Practice Strategy (Bowen, Martin, Liston, & Nelson, 2009).…”
Section: The Support and Resiliency Inventorymentioning
confidence: 99%
“…They function as resources for individuals and families in achieving their desired goals and ambitions. Support for this theory is grounded in a growing body of empirical research (Bowen, Martin, Mancini & Swick, 2015), as well as applications of the theory to practice (Huebner, Mancini, Bowen & Orthner, 2009). Figure 1 illustrates the conceptual model that is tested in this investigation.…”
Section: Conceptual Modelmentioning
confidence: 99%
“…Data from the Defense Manpower Data Center reported that from October 2001 through February 2008 there were 478 military members that died participating in Operation Enduring Freedom (Afghanistan, Philippines, Southwest Asian, and other locations) and 1,867 were wounded in action (Huebner, Mancini, Bowen & Orthner, 2009). As the Global War on Terrorism (GWOT) continues, the death rate continues to rise.…”
Section: Introductionmentioning
confidence: 99%
“…The deployment and death/wounded in action daily. As of November 2007, there were 162,000 troops deployed to Iraq and 26,000 to Afghanistan (Whitlock, 2008 as cited by Huebner, et al, 2009). Roughly, 1.5 million service members have spent service time in Iraq; about 500,000 have served two tours of combat, 70,000 have served three, and 20,000 have been deployed five or more times .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation